Kewenangan Presiden dalam Menilai Kondisi Kegentingan Yang Memaksa - Vikhy Koko Satriawan; Ahmad Sholikhin Ruslie (Jurnal Mengkaji Indonesia, 2023)
Abstract: PERPPU is the authority of the President according to Article 22 paragraph (1) of the 1945 Constitution of the Republic of Indonesia which can be stipulated based on a compelling condition of urgency. Purpose: The purpose of the research is to determine the compatibility of PERPPU Job Creation whit the Constitutional Court Decision Number 91/PUU-XVIII/2020. Design/Methodology/Approach: The type used in this research is normative legal research, and uses several approaches, namely the statute approach, conceptual approach, and historical approach. Findings: The results of this research show that in the formation of the Job Creation PERPPU there were no coercive conditions that forced it, and it was not in accordance with what was meant in the Constitutional Court Decision Number 91/PUU-XVIII/2020. Originality/Value: There has not been much research regarding the compatibility of PERPPU Job Creation whit the Constitutional Court Decision Number 91/PUU-XVIII/2020. Apart from that, this research will also explain the urgency that forced the formation of PERPPU Job Creation.